2005
DOI: 10.1529/biophysj.104.047506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Transmembrane Polypeptide Orientational Fluctuations

Abstract: The orientation and motion of a model lysine-terminated transmembrane polypeptide were investigated by molecular dynamics simulation. Recent 2H NMR studies of synthetic polypeptides with deuterated alanine side chains suggest that such transmembrane polypeptides undergo fast, axially symmetric reorientation about the bilayer normal but have a preferred average azimuthal orientation about the helix axis. In this work, interactions that might contribute to this behavior were investigated in a simulated system co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The authors showed that large deviations can exist between the actual time-averaged helix tilt and rotation angles as deduced directly from the MD traces and the calculated values that were either evaluated indirectly from the simulated 2 H-NMR splittings or obtained directly by experiment. In fact, these and other MD studies (23,24) have systematically yielded much larger tilt angles of the peptides (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) than determined from 2 H-NMR experiments of the same systems (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 88%
“…The authors showed that large deviations can exist between the actual time-averaged helix tilt and rotation angles as deduced directly from the MD traces and the calculated values that were either evaluated indirectly from the simulated 2 H-NMR splittings or obtained directly by experiment. In fact, these and other MD studies (23,24) have systematically yielded much larger tilt angles of the peptides (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) than determined from 2 H-NMR experiments of the same systems (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 88%
“…In most computational studies, WALP peptides display larger tilt angles compared to solid-state 2 H-NMR results. MD simulations provided values in the range 20-35 (20)(21)(22)(23)(24). This difference appears to be independent of the force field and other details of methods used in simulations.…”
Section: Comparison Between Simulations and Experimentsmentioning
confidence: 95%
“…Numerous atomistic simulation studies of WALP and KALP peptides in lipid bilayers have been reported (20)(21)(22)(23)(24). In all cases, the tilt angle predicted by the simulations was significantly larger (e.g.,~30 for WALP23 in DMPC (24)) than that determined from 2 H NMR (17)(18)(19).…”
Section: Introductionmentioning
confidence: 92%
“…Similar structure was deter-mined by solid-state NMR, and the tilting angle of the N-terminal a-helix was determined to be 21 (7). Other examples are the transmembrane domain of Neu (8), lysine-terminated alanine-leucine alternating polypeptide (9), hydrophobic peptides of Trp-and Lys-flanked leucine polypeptide (10), and the monomeric sarcolipin which regulates the sarcoplasmic reticulum Ca-ATPase activity (11), where the MD simulation were performed and the peptide structures and orientations were investigated. Recently, Kandasamy et al (12) investigated the structure of the second transmembrane domain of g-amino butyric acid receptor in lipid bilayers using solid-state NMR and MD simulation.…”
Section: Introductionmentioning
confidence: 92%
“…Although the fluctuation indicates that no specific interactions occur with the specific sites of the membrane, the strong interaction of Ser 1 and Lys 2 with the membrane headgroups works as an anchor to keep these residues in this region during the tilting behavior. Lys 9 and Lys 12 are more important among all hydrophilic residues for rotational and translational movements of BLT2 in the membrane bilayer, because these hydrophilic residues locate far from the interface region. The interaction energies among Lys 9 , Lys 12 , and lipid molecules were analyzed and the results were shown in Fig.…”
Section: Interactions Of Bombolitin-ii With a Membrane Bilayermentioning
confidence: 99%